Protest of the Polish-Lithuanian Commonwealth Commissioners Before the Imperial Envoy on Breaking off Peace Negotiations with Moscow in February 1616th - Nagielski, Mirosław (Verba volant, scripta manent: Księga jubileuszowa dedykowana Profesorowi Zbigniewowi Anusikowi w sześćdziesiątą piątą rocznicę urodzin, 2022)
At the turn of 11615/1616, negotiations concerning the end of hostilities between Publishing-Lithuanian commissioners and Moscow began at Smolensk with the mediation of the imperial envoy Erasmus Heide von Rassenstein (Heidelius). The Moscow side demanded the return of Smolensk, i.e. the territories occupied by the Polish-Lithuanian Commonwealth, the recognition of Michael Romanov’s rights to the tsarist throne and the release of prisoners of war led by Patriarch Filaret. These conditions were unacceptable for the Commonwealth’s commissioners, who blamed Moscow for the breakdown of the negotiations. Unsuccessful negotiations caused the war to be prolonged for another 3 years, i.e. until the end of 1618th when the peace treaty with Moscow was signed in Deulin.